PANDANGAN CIVITAS AKADEMIA UII MENGENAI CANDI KIMPULAN DI KAMPUS TERPADU UII YOGYAKARTA - Marzuki, Irfanuddin Wahid (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
The slopes of Mount Merapi are found the remains of the temple of the Ancient Mataram Kingdom. The temples are lava eruption buried for hundreds of years. One finding of the temple is a temple complex Kimpulan its Integrated Campus Indonesian Islamic University (UII) in Yogyakarta Jalan Kaliurang Km 14. Kimpulan temple discovered during the construction of the central library UII intact no damage. In this article, try to find out the views of the academic community of the existence of temples Kimpulan UII.